Perpajakan dalam Sejarah Peradaban Islam dan Potensi Penerapannya di Dunia Modern Saat Ini - Agus Niamilah; Zainal Arif (Pelantar Press, 2025)
Taxes remain the primary source of revenue for several countries around the world to fund government operations and national development, including Indonesia. Efforts to maximize state revenue are always associated with increasing tax collection. Citizens' participation in fulfilling their tax obligations is also influenced by their level of trust in public services and the provision of infrastructure, which are perceived as the realization of the taxes they pay to the state. This study employs a literature review of the concepts and taxation systems in the history of Islamic civilization, which were implemented during the leadership of Prophet Muhammad (PBUH) in Medina and continued during the Caliphate periods. The results of the literature review reveal that the concepts and systems of taxation in Islam can be adopted as contemporary tax management systems to establish a trustworthy and equitable tax system. This study also presents several alternative sources of state revenue that can be enhanced, enabling the state to reduce its reliance on taxes as the primary source of revenue